IMF Survey : Volume 28, Issue 11. (IMF Survey; IMF Survey, 1999)
Following are edited excerpts from an address given by IMF Managing Director Michel Camdessus at the twenty-fourth annual conference of the International Organization of Securities Commissions (IOSCO) in Lisbon, Portugal, on May 25. The full text is available on the IMF's website (http://www.imf.org).